1991
DOI: 10.1093/ndt/6.10.701
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Binding of Low-Density Lipoproteins to Cultured Rat Mesangial Cells

Abstract: Mesangial cell lipid accumulation is a recognised feature of glomerular disease and has been implicated as a factor in the pathogenesis of renal injury. To investigate possible mechanisms of such accumulation, binding of 125I-labelled human low-density lipoprotein (LDL) to rat mesangial cells was studied in vitro. Experiments were performed at 4 degrees C to prevent ligand internalisation. LDL remained associated with the cells after repeated washing. Binding was time-dependent, was inhibited by addition of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Recent experimental and clinical evidence suggests that inflammation is an aggravating factor in lipid-mediated peripheral cell injury, such as atherogenesis and also glomerulosclerosis, which has many similarities to atherosclerosis, as described by our group [22][23][24] and others [25,26]. Cardiovascular risk is increased in chronic inflammatory states, up to 33-fold in patients with renal failure and allograft, and 50-fold in patients with immune dysregulation (e.g., systemic lupus erythematosus) [27,28].…”
mentioning
confidence: 81%
“…Recent experimental and clinical evidence suggests that inflammation is an aggravating factor in lipid-mediated peripheral cell injury, such as atherogenesis and also glomerulosclerosis, which has many similarities to atherosclerosis, as described by our group [22][23][24] and others [25,26]. Cardiovascular risk is increased in chronic inflammatory states, up to 33-fold in patients with renal failure and allograft, and 50-fold in patients with immune dysregulation (e.g., systemic lupus erythematosus) [27,28].…”
mentioning
confidence: 81%
“…Finally, lipid-lowering therapy has been shown to improve glomerulosclerosis in the Zucker rat, a model of diabetes complicated with dyslipidemia [22]. Mesangial cells and glomerular epithelial cells (podocytes) have been shown to express receptors for TG-rich lipoproteins (TGRLs) [23][24][25][26]. TGRLs stimulate inflammatory pathways via the secretion of proinflammatory cytokines such as TNF-α, transforming growth factor (TGF)-β, and interleukin (IL)-6 [27], which results in the production of reactive oxygen species (ROS), leading to excessive ECM production.…”
Section: Impairment Of the Renal Function By Lipidsmentioning
confidence: 99%
“…Although Sprague-Dawley and obese Zuckcr rats have mainly been used for studies of lipoprotein metabolism and glomerulosclerosis, only sporadic attempts have been made to use rat cells in stud ies of atherosclerosis in the past. Wheeler et al [8] showed in single experiments that the affinity of rat LDL towards the rat mesangial cell receptor is considerably higher com pared to human LDL. These data are supported by in vivo experiments in rat which showed clearance of human LDL to be slower than that of homologous rat LDL [20].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of apoE-containing highdensity lipoproteins (HDL) in the rat along with the rela tive deficiency of apoB-containing rat low-density lipo proteins (LDL) would suggest that in this species prefera bly apoE-containing lipoproteins may supply the extrahepatic tissues with cholesterol whereas LDL might be less important. Support for these observations came from studies demonstrating that rat mesangial cells have highaffinity receptors for rat lipoproteins but bind human LDL ineffectively [8], Therefore, the purpose of this study was to investigate the interaction of human apoB-and apoB.E-containing lipoproteins with receptors of rat and human mesangial cells. Furthermore, the value of using human lipoproteins in metabolic studies with rats was the subject of this investigation.…”
Section: Introductionmentioning
confidence: 99%